Field-scale investigation of different miscible CO2-injection modes to improve oil recovery in a clastic highly heterogeneous reservoir - Jaber, A.K. (Springer Verlag, 2017)
Carbon dioxide flooding is considered one of the most commonly used miscible gas injections to improve oil recovery, and its applicability has grown significantly due to its availability, greenhouse effect and easy achievement of miscibility relative to other gases. Therefore, miscible CO2-injection is considered one of the most feasible methods worldwide. For long-term strategies in Iraq and the Middle East, most oilfields will need to improve oil recovery as oil reserves are falling. This paper presents a study of the effect of various CO2-injection modes on miscible flood performance of the highly heterogeneous clastic reservoir. An integrated field-scale reservoir simulation model of miscible flooding is accomplished for this purpose. The compositional simulator, Eclipse compositional, has been used to investigate the feasibility of applying different miscible CO2-injection modes. The process of the CO2-injection was optimized to start in January 2056 as an improved oil recovery method after natural depletion and waterflooding processes have been performed, and it will continue to January 2072. The minimum miscibility pressure was determined using empirical correlations as a function of reservoir crude oil composition and its properties. Four miscible CO2-injection modes were undertaken to investigate the reservoir performance. These modes were, namely the continuous CO2-injection (CCO2), water-alternating-CO2-injection (CO2-WAG), hybrid CO2-WAG injection, and simultaneous water and CO2-injection (CO2-SWAG) processes. All injection modes were analyzed in respect to the net present value (NPV) and net present value index (NPVI) calculations to confirm the more feasible CO2 development strategy. The results indicated that the application of CO2-SWAG injection mode of 2:1 SWAG ratio attained the highest oil recovery, NPV and NPVI, among the other modes. The achieved incremental oil recovery by this process was 9.174 , that is 189 MM STB of the oil produced higher than the waterflooding case, 1.113 (23 MMSTB of oil) in comparison with the CCO2-flooding case, 1.176 (24.3 MMSTB of oil) in comparison with the hybrid CO2-WAG case and almost 0.987 (204 MMSTB of oil) when compared with the CO2-WAG case. The results indicated that the application of CO2-WAG injection mode of 1.5:1 WAG ratio attained the highest oil recovery after the SWAG process. © 2016, The Author(s).